THE CORRELATION OF ANEMIA AND HEPCIDIN SERUM LEVELS IN REGULAR HEMODIALYSIS PATIENTS WITH CHRONIC HEPATITIS C IN HAJI ADAM MALIK HOSPITAL MEDAN - Wingsar Indrawanto; Adi Koesoema Aman; Alwi Thamrin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Background : End stage renal disease patients who undergo hemodialysis therapy are the high-risk populations who are infected by hepatitis C virus. Some studies have been reported that hepcidin levels decreased in patients with chronic hepatitis C. Hepcidin serum concentrations were also reported to increase in patients with renal failure in the line with increased severity of renal failure, which can cause the accumulation of hepcidin which culminates in anemia because iron deficiency. This Study was to analyze the correlation of anemia and hepcidin serum levels in patients end stage renal disease who undergoing regular hemodialysis with chronic hepatitis C.Methods : This study was an analytic observational with cross sectional design which was conduted on 24 patients end stage renal disease (ESRD) with chronic hepatitis C and 24 patients with ESRD without hepatitis who are undergoing regular hemodialysis theraphy in Haji Adam Malik Hospital, Medan in July – September 2016. All study subjects were examined for full blood count and hepcidin serum levels. The result of the iron status were recorded from the patient’s medical record.Result : In this study, the mean hemoglobin was 8,15±1,44 g/dL, mean hematocrit 25,42±4,53%, median hepcidin levels 29,75 (4,92-359,49) in the patients ESRD with chronic hepatitis C and mean hemoglobin 8,21±1,50 g/dL, mean hematocrit 25,25±4,37%, median hepcidin levels 30,33 (11,65-141,53) in the patients ESRD without hepatitis. In Spearman’s rho test was showed a positive correlation that significant between hepcidin and hemoglobin (r = 0,439, p = 0,032), hepcidin and hematocrit (r = 0,021, p = 0,024) in patients ESRD with chronic hepatitis C.Conclusion : This study showed there was a positive correlation between anemia and hepcidin serum levels in patients ESRD who undergoing regular hemodialysis with chronic hepatitis C.